Family Cohesion as a Mediator of the Impact of Internal Locus of Control on Students' Career Maturity: A Path Analysis - Sangadah, Rina; Sugiharto, Dwi Yuwono Puji; Mugiarso, Heru (citeus, 2025)
This study investigates the function of family cohesion as a mediator between internal locus of control and career maturity among vocational high school students. The primary aim of this study is to examine how individuals' ideas regarding their power over their life (internal locus of control) affect their preparedness to make career decisions and the degree to which familial harmony and support mediate this relationship. This study employs a quantitative methodology via a survey approach. Data were gathered from 381 twelfth-grade vocational high school students in Purbalingga Regency, Indonesia, selected through purposive sampling methods. The utilized instruments included the internal locus of control scale, the family cohesion scale, and the career maturity scale, all of which had undergone validation and reliability testing. Path analysis techniques were employed to evaluate the proposed mediation model. The research findings demonstrate that an internal locus of control significantly enhances professional maturity. Another key conclusion is that family cohesion notably mediates the association between internal locus of control and vocational maturity. Students with robust self-efficacy will exhibit enhanced career maturity, a phenomenon further amplified by a coherent and supportive familial context. This study concludes that family cohesion significantly mediates the impact of internal locus of control on the career maturity of vocational high school students.